Managing kidney disease with blood-pressure control - Wühl, Elke; Schaefer, Franz (Nature reviews. Nephrology, 2011)
Hypertension is a major risk factor for the progression of chronic kidney disease (CKD) in adults and children, and existing evidence suggests that pharmacological intervention could slow the decline in renal function. In this Review, Wühl and Schaefer discuss the pathology of CKD progression, including the role of hypertension and proteinuria. The use of tight blood-pressure control to prevent progressive CKD and the various antihypertensive agents used in patients with CKD are also discussed.
Gesehen am 05.12.2022